MANAJEMEN MASJID DI KOTA KUPANG - Anton (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2019)
Mosque is a building where the Muslims are praying and basically it is a place to do all activities which is concerned in fidelity to Allah. Besides, it is an essay institution to create the faithful people, worship to Allah, people who do charity in their society life, have character, and solidly morals. The management of the mosque is an effort to attain the target of the mosque which is to realize the society, the people who are blessed by Allah SWT through the utilities that can be donated by mosque institution with its adherents. In this concept, the management of mosque is the controlling which is include planning, organizing, administrating and supervision to create a congregation who applicable with Islam demands, the prosperous society, harmonious, peaceful, with the willing, blessing and grace of Allah SWT, so the society are able to give rahmah to nature and environs. Generally, the existing mosque management in Kupang City has been implementing the five system elements namely planning, organizing, administering, monitoring and evaluation. The most prominent system which is implemented were the organizing and administrating, while the monitoring and evaluation system were still less attention. The routine activities done by the mosques in Kupang City were praying together, praying on Friday, feast day, zakat and flesh distribution, Al-qur'an kindergarten, Kindergarten and so forth. There was no unique and new activities founded such as entrepreneurship and so on.